1997
DOI: 10.1016/s0165-2478(97)00069-2
|View full text |Cite
|
Sign up to set email alerts
|

CD148, a membrane protein tyrosine phosphatase, is able to induce tyrosine phosphorylation on human lymphocytes

Abstract: CD148 is a new cluster of differentiation defined in the VI International Workshop on Leucocyte Differentiation Antigens. It has been identified as the hematopoietic form of a formerly described membrane protein tyrosine phosphatase called HPTPp/ DEP-1. Previous data have demonstrated that this molecule is able to give rise to [Ca 2 + ] i increase. In the present work we show its capability to induce protein tyrosine phosphorylation in human lymphocytes in spite of its intrinsic protein tyrosine phosphatase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Our results showed that the crosslinking of CD148 is able to induce an increase in [Ca2+Ii as well as tyrosine phosphorylation of several substrates (20), including PLC-yl (6). It has also been shown that ligation of CD148 on T cells by immobilized, but not soluble, anti-CD148 mAb greatly augmented the in vitro pro-242 ANTON GAYA et al…”
Section: Functional Characterization Of Cd148mentioning
confidence: 61%
“…Our results showed that the crosslinking of CD148 is able to induce an increase in [Ca2+Ii as well as tyrosine phosphorylation of several substrates (20), including PLC-yl (6). It has also been shown that ligation of CD148 on T cells by immobilized, but not soluble, anti-CD148 mAb greatly augmented the in vitro pro-242 ANTON GAYA et al…”
Section: Functional Characterization Of Cd148mentioning
confidence: 61%
“…Antibodies-DEP-1 monoclonal antibodies A3 and 143-41 used for immunoprecipitations were generous gifts from Dr. Gregorio Aversa and Dr. Antoni Gayá , respectively, and were described previously (9,10). The DEP-1 polyclonal antibody CS895A was generated against the DEP-1 extracellular domain peptide (CDASNTERSRAGSPTAP) corresponding to amino acids 292-307 coupled to KLH (Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…DEP-1 comprises an extracellular segment of eight fibronectin type III repeats, a transmembrane domain, and a single cytoplasmic PTP domain. Also known as PTP- (6) and CD148 (9,10), DEP-1 is expressed in a variety of tissues and cell types. There is a growing body of evidence suggesting a role for DEP-1 in the inhibition of cell growth.…”
mentioning
confidence: 99%
“…DEP-1 is expressed at low levels in resting T cells, but is upregulated in activated T cells, and ligation with anti-DEP-1 antibodies induces proliferation of anti-CD3 activated T cells (Tangye et al, 1998a). Interestingly, transient transfection of DEP-1 has been reported to be a negative regulator of T cell activation, and also results in a reduction of TCR-mediated ERK-1 and ERK-2 activation, and reduced tyrosine phosphorylation (Palou et al, 1997;Hundt et al, 1997;Tangye et al, 1998a;Tangye et al, 1998b;Billard et al, 2000;del Pozo et al, 2000). DEP-1…”
Section: Introductionmentioning
confidence: 99%